METHOD AND FINITE ELEMENT ANALYSIS FOR THE COMPRESSION INSTABILITY ULTIMATE LOAD OF A Z-SHAPED STIFFENED-WELED PLATE - LI ZhenYuan; SONG Xin; SHEN Yang; CHEN YangLiu; ZHANG JiaZhen (Jixie qiangdu)
Object of study was the large Z shaped stiffened-welded plate,combined with theoretical analysis and finite element simulation of Abaqus researched the compression instability ultimate load,to provide theory and simulation for the application of large welded plate,save the test cost and improve efficiency. The theory studied the relationship between effective width and radius of inertia,calculation of the average load as skin with truss had different material. In the simulation of analysis,ultimate load was determined by extracting the extreme value of the load proportion factor（ LPF）. For improving the accuracy of the simulation,according to the strength of the welding seam with the cloud image judged the welding sequence,studied on the variation of ultimate load in welding,to determine the limit load range. Theoretical and the simulation value compared with the experiment. Influence of the elastic modulus of material on the overall ultimate load was analyzed,by the result of the analysis,the modulus of the long truss material is more conductive to improve the ultimate load.